A flame retardant polystyrene thermal insulation board and its preparation process
By combining chemically modified β-cyclodextrin microcapsule flame retardant with melamine-modified urea formaldehyde resin in polystyrene foam sheets, the problem of flammability of polystyrene foam sheets is solved, and its flame retardant performance is significantly improved, and its application in the fields of fire protection and flame retardant is expanded.
Patent Information
- Application Number
- CN202311032740.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-16
AI Technical Summary
Polystyrene foam boards are flammable and release toxic fumes, limiting their application in fire protection, flame retardant and other fields.
A chemically modified β-cyclodextrin microcapsule flame retardant was used to form a flame retardant coating liquid by combining with melamine-modified urea-formaldehyde resin, and combined with radiative polystyrene beads to foam, blend and mold, to prepare a flame retardant polystyrene insulation board.
It significantly improves the flame retardant performance of polystyrene insulation boards and enhances its application potential in fire protection, flame retardant and other fields.
Smart Images

Figure SMS_1 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, in particular to a flame retardant polystyrene thermal insulation board and a preparation process thereof. Background Art
[0002] Polystyrene foam board has the advantages of light weight, low cost, low thermal conductivity, good thermal insulation and electrical insulation properties. It is a building material with excellent comprehensive performance and is widely used in construction, insulation, packaging, daily necessities and other fields. However, polystyrene foam board has problems such as easy combustion and release of toxic smoke, which is not conducive to its application in fire protection, flame retardant and other fields. Therefore, it is necessary to develop new halogen-free environmentally friendly flame retardants, such as expansion flame retardants, silicon-based flame retardants, bio-based flame retardants, etc.
[0003] β-cyclodextrin is a non-toxic and environmentally friendly natural macromolecule with high carbon-forming ability, hydrophobicity inside the cavity and hydrophilicity outside the cavity, which enables it to encapsulate a variety of organic compounds. It has broad application prospects in microcapsules, flame retardants, drug separation and enrichment, and drug sustained release. Chemical modification of β-cyclodextrin is an effective method to increase its encapsulation capacity for characteristic compounds, which can expand its practical application in flame retardants, polymer materials, etc. Summary of the invention
[0004] The technical problem solved by the invention is: a cyclodextrin microcapsule flame retardant is prepared to enhance the flame retardant performance of a polystyrene thermal insulation board.
[0005] The technical solution of the present invention is:
[0006] A preparation process of a flame retardant polystyrene thermal insulation board, the flame retardant polystyrene thermal insulation board comprising 75-90 parts by weight of expandable polystyrene beads and 10-25 parts by weight of a melamine-modified urea-formaldehyde resin flame retardant coating liquid; the preparation process is:
[0007] S1, adding melamine modified urea formaldehyde resin and cyclodextrin microcapsule flame retardant into a blender and mixing them evenly to obtain a melamine modified urea formaldehyde resin flame retardant coating liquid;
[0008] S2. Pre-foam the expandable polystyrene beads in a water vapor system at 100°C for 3-6 minutes, then mature the expandable polystyrene beads at room temperature for 18-24 hours, and then mix them with the melamine-modified urea-formaldehyde resin flame-retardant coating liquid in a mixer, and compression-mold the materials in a flat vulcanizer to obtain a flame-retardant polystyrene insulation board.
[0009] Furthermore, in S1, the stirring rate is controlled to be 80-150 r / min, and the stirring time is 5-10 min; in S2, the stirring rate is controlled to be 200-300 r / min, and the stirring time is 30-60 min.
[0010] Furthermore, during the molding in S2, the temperature is controlled to be 100-120° C., the pressure is 7-10 MPa, and the time is 3-5 min.
[0011] Furthermore, the preparation process of the cyclodextrin microcapsule flame retardant is:
[0012] (1) Naphthalene-2,6-dicarboxaldehyde and histidine are added to ethanol, glacial acetic acid is added dropwise, and the mixture is refluxed at 70-80° C. for 2-5 hours. The ethanol is removed by concentration, and water and dichloromethane are added for extraction. The organic phase is concentrated, washed with petroleum ether, and dried to obtain a naphthalene-2,6-histidine intermediate.
[0013]
[0014] (2) Add β-cyclodextrin, naphthalene-2,6-histidine intermediate, N-hydroxysuccinimide, and dicyclohexylcarbodiimide to dimethyl sulfoxide, react at a temperature of 35-50° C. for 24-48 hours, filter, wash with ethanol, and dry to obtain naphthalene-histidine cross-linked cyclodextrin.
[0015] (3) Add naphthalene-histidine cross-linked cyclodextrin and 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to water. Ultrasonic vibration is performed for 0.5-1h, and then stirred for 12-24h, filtered, washed with ethanol, and dried to obtain a cyclodextrin microcapsule flame retardant.
[0016] Furthermore, the ratio of the reactants in (1) is: naphthalene-2,6-dicarboxaldehyde: histidine: glacial acetic acid = 1 g: (1.7-2.5) g: (0.1-0.18) mL.
[0017] Furthermore, the ratio of each reactant in (2) is β-cyclodextrin, naphthalene-2,6-histidine intermediate, N-hydroxysuccinimide, dicyclohexylcarbodiimide = 1g: (0.8-2.5)g: (0.3-1)g: (0.7-2.2)g.
[0018] Furthermore, the ratio of the reactants in (3) is naphthalene-histidine cross-linked cyclodextrin: 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide = 1 g: (0.5-1.5) g.
[0019] The beneficial technical effect of the present invention is: using naphthalene-2,6-histidine intermediate as a crosslinking agent, utilizing its two carboxyl groups to react with the hydroxyl groups of β-cyclodextrin to undergo esterification crosslinking reaction, obtaining naphthalene-histidine crosslinked cyclodextrin, and the crosslinked cyclodextrin forms a microcapsule structure of a spatial crosslinked network structure, with a larger specific surface area and more embedding sites, and the oxygen atoms in its imidazole NH bond and ester group can interact with the hydroxyl groups of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to undergo hydrogen bond interaction, thereby increasing the embedding amount and obtaining a cyclodextrin microcapsule flame retardant. It is compounded with melamine-modified urea-formaldehyde resin to form a flame-retardant coating liquid, and foamed, blended, and molded with expandable polystyrene beads to obtain a flame-retardant polystyrene insulation board.
[0020] Naphthalene-histidine cross-linked cyclodextrin contains a rigid naphthalene ring structure with a high carbon content, which can improve the carbonization of cyclodextrin during combustion. Its imidazole structure forms an expanding flame retardant system with 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide, which improves the limiting oxygen index and carbonization effect of polystyrene insulation boards during combustion, reduces the combustion heat release rate, and improves the flame retardant effect of the boards, making polystyrene boards better used in fire protection, flame retardancy and other fields. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] (1) Add 4 g of naphthalene-2,6-dicarboxaldehyde and 8.5 g of histidine to 50 mL of ethanol, add 0.6 mL of glacial acetic acid dropwise, reflux at 70° C. for 4 h, concentrate to remove ethanol, add water and dichloromethane, extract, concentrate the organic phase, wash with petroleum ether, and dry to obtain a naphthalene-2,6-histidine intermediate.
[0024] (2) Add 5 g of β-cyclodextrin, 4 g of naphthalene-2,6-histidine intermediate, 1.5 g of N-hydroxysuccinimide, and 3.5 g of dicyclohexylcarbodiimide to 100 mL of dimethyl sulfoxide, react at 40° C. for 36 h, filter, wash with ethanol, and dry to obtain naphthalene-histidine cross-linked cyclodextrin.
[0025] (3) Add 5 g of naphthalene-histidine cross-linked cyclodextrin and 2.5 g of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to 200 mL of water. The mixture was ultrasonically shaken for 0.5 h, then stirred for 24 h, filtered, washed with ethanol, and dried to obtain a cyclodextrin microcapsule flame retardant.
[0026] (4) adding melamine-modified urea-formaldehyde resin and cyclodextrin microcapsule flame retardant into a blender and mixing them evenly, controlling the stirring rate to 80 r / min and the stirring time to 8 min, and stirring evenly to obtain a melamine-modified urea-formaldehyde resin flame retardant coating liquid;
[0027] (5) 90 parts by weight of expandable polystyrene beads were pre-foamed in a water vapor system at 100°C for 4 minutes, and then the expandable polystyrene beads were aged at room temperature for 24 hours, and then mixed with 10 parts of melamine-modified urea-formaldehyde resin flame retardant coating liquid in a mixer, the stirring rate was controlled to 250 r / min, the stirring time was 60 minutes, and the material was compression molded in a flat vulcanizer, the temperature was controlled to 100°C, the pressure was controlled to 8 MPa, and the time was controlled to 4 minutes to obtain a flame retardant polystyrene insulation board.
[0028] Example 2
[0029] (1) Add 4 g of naphthalene-2,6-dicarboxaldehyde and 6.8 g of histidine to 80 mL of ethanol, add 0.72 mL of glacial acetic acid dropwise, reflux at 80° C. for 5 h, concentrate to remove ethanol, add water and dichloromethane, extract, concentrate the organic phase, wash with petroleum ether, and dry to obtain a naphthalene-2,6-histidine intermediate.
[0030] (2) Add 5 g of β-cyclodextrin, 8 g of naphthalene-2,6-histidine intermediate, 3.5 g of N-hydroxysuccinimide, and 7 g of dicyclohexylcarbodiimide to 150 mL of dimethyl sulfoxide, react at 35° C. for 48 h, filter, wash with ethanol, and dry to obtain naphthalene-histidine cross-linked cyclodextrin.
[0031] (3) Add 5 g of naphthalene-histidine cross-linked cyclodextrin and 5 g of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to 200 mL of water, ultrasonically shake for 0.5 h, then stir for 24 h, filter, wash with ethanol, and dry to obtain a cyclodextrin microcapsule flame retardant.
[0032] (4) adding melamine-modified urea-formaldehyde resin and cyclodextrin microcapsule flame retardant into a blender and mixing them evenly, controlling the stirring rate to be 100 r / min, the stirring time to be 8 min, and stirring evenly to obtain a melamine-modified urea-formaldehyde resin flame retardant coating liquid;
[0033] (5) 85 parts by weight of expandable polystyrene beads were pre-foamed in a water vapor system at 100°C for 4 minutes, and then the expandable polystyrene beads were aged at room temperature for 24 hours, and then mixed with 15 parts of melamine-modified urea-formaldehyde resin flame retardant coating liquid in a mixer, the stirring rate was controlled to 250 r / min, the stirring time was 60 minutes, and the material was compression molded in a flat vulcanizer, the temperature was controlled to 120°C, the pressure was controlled to 8 MPa, and the time was controlled to 4 minutes to obtain a flame retardant polystyrene insulation board.
[0034] Example 3
[0035] (1) Add 4 g of naphthalene-2,6-dicarboxaldehyde and 10 g of histidine to 80 mL of ethanol, add 0.6 mL of glacial acetic acid dropwise, reflux at 70° C. for 5 h, concentrate to remove ethanol, add water and dichloromethane, extract, concentrate the organic phase, wash with petroleum ether, and dry to obtain a naphthalene-2,6-histidine intermediate.
[0036] (2) Add 5 g of β-cyclodextrin, 12.5 g of naphthalene-2,6-histidine intermediate, 5 g of N-hydroxysuccinimide, and 11 g of dicyclohexylcarbodiimide to 200 mL of dimethyl sulfoxide, react at 50° C. for 24 h, filter, wash with ethanol, and dry to obtain naphthalene-histidine cross-linked cyclodextrin.
[0037] (3) Add 5 g of naphthalene-histidine cross-linked cyclodextrin and 7.5 g of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to 200 mL of water, ultrasonically shake for 0.5 h, then stir for 24 h, filter, wash with ethanol, and dry to obtain a cyclodextrin microcapsule flame retardant.
[0038] (4) adding melamine-modified urea-formaldehyde resin and cyclodextrin microcapsule flame retardant into a blender and mixing them evenly, controlling the stirring rate to be 100 r / min, the stirring time to be 8 min, and stirring evenly to obtain a melamine-modified urea-formaldehyde resin flame retardant coating liquid;
[0039] (5) 75 parts by weight of expandable polystyrene beads were pre-foamed in a water vapor system at 100°C for 4 minutes, and then the expandable polystyrene beads were aged at room temperature for 24 hours, and then mixed with 25 parts of melamine-modified urea-formaldehyde resin flame retardant coating liquid in a mixer, the stirring rate was controlled to 250 r / min, the stirring time was 60 minutes, and the material was compression molded in a flat vulcanizer, the temperature was controlled to 100°C, the pressure was controlled to 8 MPa, and the time was controlled to 4 minutes to obtain a flame retardant polystyrene insulation board.
[0040] Comparative Example 1: The difference from Example 1 is that no cyclodextrin microcapsule flame retardant is added.
[0041] Comparative Example 2: The difference from Example 1 is that β-cyclodextrin is used instead of cyclodextrin microcapsule flame retardant.
[0042] Comparative Example 3: The difference from Example 1 is that naphthalene-histidine cross-linked cyclodextrin is used instead of the cyclodextrin microcapsule flame retardant.
[0043] Comparative Example 4: The difference from Example 1 is that 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide is used instead of the cyclodextrin microcapsule flame retardant.
[0044] Comparative Example 5:
[0045] (1) Add 5 g of β-cyclodextrin and 2.5 g of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to 200 mL of water. The mixture was ultrasonically shaken for 0.5 h, then stirred for 24 h, filtered, washed with ethanol, and dried to obtain a cyclodextrin flame retardant.
[0046] (2) adding melamine-modified urea-formaldehyde resin and cyclodextrin flame retardant into a mixer and mixing them evenly, controlling the stirring rate to 100 r / min and the stirring time to 8 min, and stirring evenly to obtain a melamine-modified urea-formaldehyde resin flame retardant coating liquid;
[0047] (3) 90 parts by weight of expandable polystyrene beads were pre-foamed in a water vapor system at 100°C for 4 minutes, and then the expandable polystyrene beads were aged at room temperature for 24 hours, and then mixed with 10 parts of melamine-modified urea-formaldehyde resin flame retardant coating liquid in a mixer, the stirring rate was controlled to 250 r / min, the stirring time was 60 minutes, and the material was compression molded in a flat vulcanizer, the temperature was controlled to 100°C, the pressure was controlled to 8 MPa, and the time was controlled to 4 minutes to obtain a flame retardant polystyrene insulation board.
[0048] The cyclodextrin microcapsule flame retardant prepared in step (3) of Example 1-3 and the cyclodextrin flame retardant prepared in step (1) of Comparative Example 5 were weighed (m) respectively, and the embedding rate Q of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide was calculated, Q=(mm 0 ) / m 0 , m 0 is the mass of naphthalene-histidine cross-linked cyclodextrin or β-cyclodextrin (5 g).
[0049]
[0050] As the amount of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide increases, the embedding amount of naphthalene-histidine cross-linked cyclodextrin prepared in Examples 1-3 increases first and then stabilizes, reaching 0.378-0.722 g / g. However, the embedding amount of Comparative Example 5 is only 0.226 g / g, because naphthalene-histidine cross-linked cyclodextrin has a spatial cross-linked network structure, a larger specific surface area, more embedding sites, and contains imidazole and ester functional groups, which can interact with the hydroxyl groups of 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide by hydrogen bonding, thereby increasing the embedding amount.
[0051] The flame retardancy of polystyrene insulation board was tested by oxygen index tester and cone calorimeter. The compressive strength was tested by universal material testing machine.
[0052]
[0053]
[0054] Compared with Comparative Example 1, as the amount of melamine-modified urea-formaldehyde resin flame retardant coating liquid in Examples 1-3 polystyrene insulation boards gradually increases, the limiting oxygen index and residual carbon content of the polystyrene insulation boards become larger and larger, with the maximum being 28.9 and 11.3%, and the peak value of the heat release rate becomes smaller and smaller, with the minimum being only 92.7 kW / m 2 , with excellent flame retardant properties. This is because the cyclodextrin microcapsule flame retardant in the coating liquid contains rigid naphthalene rings and imidazole groups, which form an expansion flame retardant system with the coated 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide, which significantly improves the carbonization effect and flame retardancy of the board. As the amount of melamine-modified urea-formaldehyde resin flame retardant coating liquid gradually increases, the compressive strength of the board will decrease, so the amount of coating liquid should not be too large.
[0055] In comparison example 2, only β-cyclodextrin was added, in comparison example 3, only cyclodextrin cross-linked with naphthalene-histidine was added, and in comparison example 4, only 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide was added. None of them formed an expanding flame retardant system, so the charring effect and flame retardancy of the polystyrene insulation board were poor.
[0056] In Comparative Example 5, only cyclodextrin flame retardant is added. The cyclodextrin does not form a spatial cross-linked network structure, nor does it contain imidazole groups or ester groups. It cannot form hydrogen bond interactions with 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide. Therefore, the coating amount is small. Although the flame retardancy of the board can be improved, the flame retardant effect is not as good as that of Example 1.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing a flame retardant polystyrene thermal insulation board, characterized in that: The flame retardant polystyrene thermal insulation board comprises the following parts by weight: 75-90 parts of expandable polystyrene beads and 10-25 parts of melamine modified urea-formaldehyde resin flame retardant coating liquid; The preparation process is as follows: S1, adding melamine-modified urea-formaldehyde resin and cyclodextrin microcapsule flame retardant into a blender and mixing them evenly to obtain a melamine-modified urea-formaldehyde resin flame retardant coating liquid; S2, pre-foaming the expandable polystyrene beads in a water vapor system, then ripening the expandable polystyrene beads at room temperature, and then mixing them with a melamine-modified urea-formaldehyde resin flame-retardant coating liquid in a mixer, and compression molding the materials in a flat vulcanizer to obtain a flame-retardant polystyrene insulation board; The preparation process of the cyclodextrin microcapsule flame retardant is as follows: (1) adding naphthalene-2,6-dicarboxaldehyde and histidine to ethanol, adding glacial acetic acid dropwise, reflux at 70-80° C. for 2-5 hours, concentrating to remove ethanol, adding water and dichloromethane, extracting, concentrating the organic phase, washing with petroleum ether, and drying to obtain a naphthalene-2,6-histidine intermediate; (2) adding β-cyclodextrin, naphthalene-2,6-histidine intermediate, N-hydroxysuccinimide, and dicyclohexylcarbodiimide to dimethyl sulfoxide, reacting at a temperature of 35-50° C. for 24-48 hours, filtering, washing with ethanol, and drying to obtain naphthalene-histidine cross-linked cyclodextrin; (3) adding naphthalene-histidine cross-linked cyclodextrin and 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide to water, ultrasonically shaking for 0.5-1h, then stirring for 12-24h, filtering, washing with ethanol, and drying to obtain a cyclodextrin microcapsule flame retardant; The ratio of each reactant in (1) is: naphthalene-2,6-dicarboxaldehyde: histidine: glacial acetic acid = 1 g: (1.7-2.5) g: (0.1-0.18) mL; The ratio of each reactant in (2) is β-cyclodextrin, naphthalene-2,6-histidine intermediate, N-hydroxysuccinimide, dicyclohexylcarbodiimide = 1 g: (0.8-2.5) g: (0.3-1) g: (0.7-2.2) g; The ratio of each reactant in (3) is naphthalene-histidine cross-linked cyclodextrin: 2,6,7-trioxa-1-phosphabicyclo (2.2.2) octane-4-methanol-1-oxide = 1g: (0.5-1.5)g.
2. The process for preparing the flame retardant polystyrene thermal insulation board according to claim 1, characterized in that: In S1, the stirring rate is controlled to be 80-150 r / min, and the stirring time is 5-10 min; in S2, the stirring rate is controlled to be 200-300 r / min, and the stirring time is 30-60 min.
3. The process for preparing the flame retardant polystyrene thermal insulation board according to claim 1, characterized in that: During the molding in S2, the temperature is controlled to be 100-120° C., the pressure is 7-10 MPa, and the time is 3-5 min.
Citation Information
Patent Citations
Flame-retardant and environment-friendly polystyrene foam material and preparation method thereof
CN107880424A
Bio-based macromolecular modified nano zirconium phosphate flame retardant and fireproof coating prepared by using bio-based macromolecular modified nano zirconium phosphate flame retardant
CN113831597A